Cycloolefin copolymer composite material

By blending SBC with COC and adding SEBS and SEPS to form a composite material, the problem of high brittleness of COC materials is solved, and its toughness and comprehensive mechanical properties are significantly improved, and production efficiency and product quality are improved.

CN119912782APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311416341.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Due to its high brittleness, cycloolefin copolymer (COC) materials are prone to damage during injection molding and precision processing, affecting production efficiency and product quality.

Method used

A composite material is formed by blending styrene-butadiene copolymer (SBC) with cycloolefin copolymer (COC) and adding hydrogenated styrene-butadiene-styrene copolymer (SEBS) and styrene-ethylene/propylene-styrene copolymer (SEPS) to improve the toughness and comprehensive mechanical properties of COC.

Benefits of technology

This method significantly improves the toughness and notch impact strength of COC composite materials, reduces the elastic modulus, improves the shrinkage rate and dimensional accuracy of the products, and is simple and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure FDA0004519654610000011
    Figure FDA0004519654610000011
Patent Text Reader

Abstract

The invention discloses a cycloolefin copolymer composite material which is characterized by comprising the following components in parts by mass: 80-95 parts of cycloolefin copolymer, 5-20 parts of styrene-butadiene copolymer, 0-9.1 parts of hydrogenated styrene-butadiene-styrene copolymer and 0-2.4 parts of styrene-ethylene / propylene-styrene copolymer. In the composite material, the hydrogenated styrene-butadiene-styrene copolymer and the styrene-ethylene / propylene-styrene copolymer can achieve a certain compatibilization effect on a blending system of the styrene-butadiene copolymer and the cycloolefin copolymer, and the purpose of synergistic toughening is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copolymers, and more particularly to a cyclic olefin copolymer composite material. Background Art

[0002] Cyclic olefin copolymer (COC) is an amorphous polymer prepared by copolymerizing norbornene or its derivatives with ethylene or α-olefins. COC has excellent mechanical properties, high transparency, low dielectric loss, low hygroscopicity, and good solvent resistance, and has many applications in the fields of medical devices, packaging, and electronic devices.

[0003] Due to the presence of cyclic rigid groups in the main chain of COC, COC materials are brittle, which has an adverse effect on the processing and application of COC. Especially in the injection molding process, the high rigidity and high brittleness of COC lead to a high breakage rate of the product during demolding after molding, which seriously reduces production efficiency. In the precision processing of COC, due to its excessive brittleness, it will either directly cause breakage or generate defects in the product, seriously affecting the final use of the product. Therefore, how to improve the toughness of COC is a problem that people need to consider.

[0004] In order to improve the toughness of COC, researchers have considered using a variety of elastomers to toughen and modify COC based on its molecular structure and performance characteristics, but none of them have achieved a balance in the comprehensive mechanical properties of COC.

[0005] CN202010765143.7 patent application discloses a method for toughening COC using EPDM, polyisobutylene rubber, polybutene rubber, etc., and its processing technology is relatively special. The method first freezes EPDM, polyisobutylene rubber, and polybutene rubber into solids in liquid nitrogen, then adds them into a pelletizer and cuts them into small particles (macroscopic size), and then blends them with COC using a twin-screw extruder to obtain a high-toughness COC composite material with high transmittance. Since COC is not completely compatible with the rubber, their blends are difficult to reach the level of molecular compatibility, and the refractive index of COC is as high as more than 1.5, and the refractive index of the rubber is relatively low, and its addition in COC will inevitably lead to phase separation, thereby affecting its transparency.

[0006] Patent application CN202010242865.4 discloses a method of using ethylene-butyl acrylate copolymer as a toughening component, glycidyl methacrylate grafted hydrogenated styrene-butadiene-styrene copolymer as a compatibilizer, and necessary processing aids to try to improve the toughness of COC while maintaining its transparency. This method has the problem that COC and ethylene-butyl acrylate copolymer, glycidyl methacrylate grafted hydrogenated styrene-butadiene-styrene copolymer, etc. are also difficult to achieve molecular compatibility, and the refractive index of each raw material is significantly different.

[0007] WO2022 / 105149A1 discloses a method of using styrene-butadiene-styrene block copolymer (SBS, PS content 28-33%, etc.), styrene-ethylene-butadiene-styrene block copolymer, POE, etc. as toughening components, adding maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene compatibilizer and even maleic anhydride grafted COC with a grafting rate of 1-2%, and the method obtains a COC composite material with high impact strength. This method also has the problem that the added components cannot achieve molecular compatibility with COC, and the difference in the refractive index of each component in the presence of phase separation will inevitably lead to a significant decrease in its optical properties, especially due to incompatibility with COC, the addition of maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene compatibilizer will only aggravate the decline in its optical properties. Summary of the invention

[0008] The inventors found, based on a large number of experiments, that styrene-butadiene copolymer (SBC) and cycloolefin copolymer (COC) have certain compatibility and can be used to toughen COC, while the solubility parameters of SEBS and SEPS are closer to COC than SBC, and their macromolecular chains contain a certain proportion of styrene repeating units, and they are also very compatible with SBC, that is, they can be used to compatibilize the COC and SBC blend system, and can also play a certain toughening role. Based on this, the present invention is formed.

[0009] Therefore, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a cycloolefin copolymer composite material that achieves a balance of COC comprehensive mechanical properties while improving toughness.

[0010] In order to achieve the purpose of the present invention, the present invention provides a cyclic olefin copolymer composite material, characterized in that it mainly includes the following components:

[0011]

[0012] In the cycloolefin copolymer composite material provided by the present invention, the cycloolefin copolymer is a cycloolefin copolymer with a norbornene content of more than 70%. The preferred cycloolefin copolymer has a glass transition temperature of 70 to 160°C (DSC method, heating rate 10°C / min) and a melt flow rate of 4 to 50g / 10min (260°C, 2.16kg); the more preferred cycloolefin copolymer has a glass transition temperature of 131±5°C (DSC method, heating rate 10°C / min) and a melt flow rate of 45±5g / 10min (260°C, 2.16kg). Examples of cycloolefin copolymers that are not limited to COC 5013L-10 produced by TOPAS Advanced Polymers in Germany have a glass transition temperature of 134°C (DSC method, heating rate 10°C / min) and a melt flow rate of 48g / 10min (260°C, 2.16kg).

[0013] In the cycloolefin copolymer composite material provided by the present invention, the styrene-butadiene copolymer (SBC), as a toughening component, contains styrene repeating units with similar structures to the cyclic groups in the cycloolefin copolymer (COC), has certain compatibility, and can be used for toughening COC. Preferably, the styrene-butadiene copolymer (SBC) has a melt flow rate of ≥8g / 10min (200°C, 5kg) and a Vicat softening point of ≥85°C (50°C / hr, ISO 306). An example but not limited to styrene-butadiene copolymer is SBC-PB5903 produced by Chimei Hard Plastics, which has a melt flow rate of 10g / 10min (200°C, 5kg), a Vicat softening point of 93°C (50°C / hr, ISO 306), and a notched impact strength of 2.3kJ / m 2 (ISO 180 / 1A).

[0014] In the cycloolefin copolymer composite material provided by the present invention, the solubility parameters of hydrogenated styrene-butadiene-styrene copolymer (SEBS) and styrene-ethylene / propylene-styrene copolymer (SEPS) are closer to COC (van Krevelen method: δ COC =16.840(J / cm 3 ) 0.5 , δ SBC =18.861(J / cm 3 ) 0.5 , δ SEBS =18.479(J / cm 3 ) 0.5 , δ SEPS =18.144(J / cm 3 ) 0.5), and the macromolecular chains of SEBS and SEPS both contain a certain proportion of styrene repeating units, and they are also very compatible with SBC, that is, they can be used to increase the volume of COC and SBC blending systems, and can also play a certain toughening role.

[0015] Preferably, the hydrogenated styrene-butadiene-styrene copolymer (SEBS) has a styrene content of 30±5% and a hardness of less than 75 (shore A). An example but not limited to hydrogenated styrene-butadiene-styrene copolymer is SEBS YH-502T produced by Sinopec Baling Petrochemical, which has a styrene content of 30% and a hardness of 73 (shore A).

[0016] Preferably, the styrene-ethylene / propylene-styrene copolymer (SEPS) has a styrene content of 30±5% and a hardness of less than 80 (shoreA). An example but not limited to styrene-ethylene / propylene-styrene copolymer is SEPS YH-4052 produced by Sinopec Baling Petrochemical, which has a styrene content of 33%, a number average molecular weight of 105,000, and a hardness of 78 (shoreA).

[0017] The inventors also unexpectedly discovered that if styrene-butadiene copolymer (SBC) is added alone, only the elongation at break of COC material can be improved, and the toughening effect is not significant. After adding hydrogenated styrene-butadiene-styrene copolymer (SEBS), the synergistic toughening effect is obvious; further, hydrogenated styrene-butadiene-styrene copolymer (SEBS) and styrene-ethylene / propylene-styrene copolymer (SEPS) are added at the same time, and the ratio of SEBS to SEPS is 2.5-3.5:1, especially 3:1. The toughening effect is better, that is, the addition of SEBS and SEPS can improve the particle size and particle distribution of rubber, enhance the toughening of the elastomer, and produce a synergistic toughening effect.

[0018] The cyclic olefin copolymer composite material of the present invention can be obtained by a method comprising the following steps:

[0019] (1) adding the pre-weighed cyclic olefin copolymer, styrene-butadiene copolymer, and optionally added hydrogenated styrene-butadiene-styrene copolymer and styrene-ethylene / propylene-styrene copolymer to a high-speed mixer in sequence, blending at 30 to 50° C., at a speed of 300 to 600 rpm, for a mixing time of 3 to 5 minutes, to obtain a premix of a cyclic olefin copolymer composite material;

[0020] (2) The premix obtained in step (1) is extruded into pellets using a twin-screw extruder with a length-to-diameter ratio of 40:1 and a screw diameter of 21.7 mm; the feeder speed is set to 5 to 20 rpm, and the screw speed is 150 to 300 rpm; the temperature of each section in the extruder is set to 180° C., 200° C., 210° C., 210° C., 220° C., 220° C., 230° C., 230° C., 230° C., 230° C., in sequence from the feed section to the die head; the premix is ​​water-cooled, pelletized, and then dried to obtain the cycloolefin copolymer composite material.

[0021] The composite material provided by the present invention has the following advantages and effects:

[0022] (1) Styrene-butadiene copolymer (SBC) has good compatibility with COC, and its elastomeric nature can promote the energy dissipation of the cycloolefin copolymer matrix and improve the toughness of COC.

[0023] (2) Hydrogenated styrene-butadiene-styrene copolymer (SEBS) and styrene-ethylene / propylene-styrene copolymer (SEPS) can have a certain compatibilizing effect on the SBC / COC blend system. At the same time, the particle size and distribution state of the dispersed phase can be adjusted according to the dosage, thereby achieving the purpose of synergistic toughening. The unnotched impact toughness of the COC composite material is significantly improved, and the notched impact strength that characterizes the notch sensitivity is also improved.

[0024] (3) When the elastic modulus of the COC composite material is reduced within a controllable range, it is beneficial to remove the product from the injection mold.

[0025] (4) By using composite modified COC such as SBC, SEBS, and SEPS, the shrinkage rate of the resulting products can be effectively improved and the dimensional deviation of the products can be significantly reduced.

[0026] (5) The composite material provided by the present invention can be simply obtained by conventional preparation methods, and the raw materials do not need additional processing, and are easy to produce on a large scale. DETAILED DESCRIPTION

[0027] The present invention will be further explained below by way of examples, but the contents of the present invention are not limited thereto.

[0028] In the embodiment, the cycloolefin copolymer is COC 5013L-10 produced by TOPAS Advanced Polymers of Germany, with a glass transition temperature of 134°C (DSC method, heating rate 10°C / min), a melt flow rate of 48g / 10min (260°C, 2.16kg), and a norbornene content of more than 70%.

[0029] In the embodiment, the styrene-butadiene copolymer is SBC-PB5903 produced by Chimei Plastics, which has a melt flow rate of 10 g / 10 min (200° C., 5 kg), a Vicat softening point of 93° C. (50° C. / hr, ISO 306), and a notched impact strength of 2.3 kJ / m 2 (ISO 180 / 1A).

[0030] In the embodiment, the hydrogenated styrene-butadiene-styrene copolymer is SEBSYH-502T produced by Sinopec Baling Petrochemical, which has a styrene content of 30% and a hardness of 73 (shore A).

[0031] In the embodiment, the styrene-ethylene / propylene-styrene copolymer is SEPSYH-4052 produced by Sinopec Baling Petrochemical, which has a styrene content of 33%, a number average molecular weight of 105,000, and a hardness of 78 (shore A).

[0032] The test results of melt flow rate in the examples and comparative examples are from a Zwick Roell Mflow melt indexer, the test results of tensile properties are from an Instron 5967 universal material testing machine, and the cantilever beam impact test results are from an Instron CEAST 9050 pendulum impact tester.

[0033] The following are the national standards for testing related performance:

[0034] Melt flow rate: GB / T 3682.1-2018;

[0035] Standard specimen preparation: GB / T 17037.1-2019

[0036] Tensile properties: GB / T 1040.1-2018;

[0037] Izod beam impact strength: GB / T 1843-2008.

[0038] Example 1

[0039] Weigh the raw materials according to the following ratio: 95 parts by mass of cycloolefin copolymer and 5 parts by mass of SBC. Mix the cycloolefin copolymer and SBC at 35°C, at a speed of 300 rpm, and mix for 5 minutes. Then, add the mixed material from the feeder to the twin-screw extruder for extrusion granulation. The process conditions are set as follows: feeder speed 8 rpm, screw speed 200 rpm, and extruder temperature of each section 180-230°C. After water cooling, pelletizing and drying, the cycloolefin copolymer composite material is obtained.

[0040] The dried polymer particles were injection molded to obtain mechanical test specimens and optical specimens (the same below): the width of the tensile specimen was 10 mm, the thickness was 4 mm, and the tensile rate was 5 mm / min. The width of the notched impact specimen was 8.5 mm, the thickness was 3 mm, and the specification of the impact pendulum was 1J.

[0041] The test results are shown in Table 1.

[0042] Example 2

[0043] Weigh the raw materials according to the following ratio: 90 parts by mass of cycloolefin copolymer and 10 parts by mass of SBC. Mix the cycloolefin copolymer and SBC at 50°C, at a speed of 600 rpm, and mix for 3 minutes. Then, add the mixed material from the feeder to the twin-screw extruder for extrusion granulation. The process conditions are set as follows: feeder speed 8 rpm, screw speed 200 rpm, and temperature of each section of the extruder 180-230°C. After water cooling, pelletizing and drying, the cycloolefin copolymer composite material is obtained.

[0044] The test results are shown in Table 1.

[0045] Example 3

[0046] Weigh the raw materials according to the following ratio: 80 parts by mass of cycloolefin copolymer and 20 parts by mass of SBC. Mix the cycloolefin copolymer and SBC at 40°C, at a speed of 400 rpm, and mix for 3 minutes. Then, add the mixed material from the feeder to the twin-screw extruder for extrusion granulation. The process conditions are set as follows: feeder speed 8 rpm, screw speed 200 rpm, and temperature of each section of the extruder 180-230°C. After water cooling, pelletizing and drying, the cycloolefin copolymer composite material is obtained.

[0047] The test results are shown in Table 1.

[0048] Example 4

[0049] Weigh the raw materials according to the following ratio: 85.7 parts by mass of cycloolefin copolymer, 9.5 parts by mass of SBC, and 4.8 parts by mass of SEBS. Mix the cycloolefin copolymer, SBS and SEBS at 35°C, at a speed of 350 rpm, and mix for 4 minutes. Then, add the mixed material from the feeder to the twin-screw extruder for extrusion granulation. The process conditions are set as follows: feeder speed 8 rpm, screw speed 200 rpm, and extruder temperature of each section 180-230°C. After water cooling, pelletizing and drying, the cycloolefin copolymer composite material is obtained.

[0050] The test results are shown in Table 1.

[0051] Example 5

[0052] Weigh the raw materials according to the following ratio: 81.8 parts by mass of cycloolefin copolymer, 9.1 parts by mass of SBC, and 9.1 parts by mass of SEBS. Mix the cycloolefin copolymer, SBS and SEBS at 40°C, at a speed of 400 rpm, and mix for 5 minutes. Then, add the mixed material from the feeder to the twin-screw extruder for extrusion granulation. The process conditions are set as follows: feeder speed 8 rpm, screw speed 200 rpm, and extruder temperature of each section 180-230°C. After water cooling, pelletizing and drying, the cycloolefin copolymer composite material is obtained.

[0053] The test results are shown in Table 1.

[0054] Example 6

[0055] Weigh each raw material according to the following ratio: 85.7 parts by mass of cycloolefin copolymer, 9.5 parts by mass of SBC, 2.4 parts by mass of SEBS, and 2.4 parts by mass of SEPS. Mix cycloolefin copolymer, SBC, SEBS and SEPS at 30°C, at a speed of 300 rpm, and mix for 5 minutes. Then, add the mixed material from the feeder to the twin-screw extruder for extrusion granulation. The process conditions are set as follows: feeder speed 8 rpm, screw speed 200 rpm, and extruder temperature of each section 180-230°C. After water cooling, pelletizing and drying, a cycloolefin copolymer composite material is obtained.

[0056] The test results are shown in Table 1.

[0057] Example 7

[0058] Weigh each raw material according to the following ratio: 81.8 parts by mass of cycloolefin copolymer, 9.1 parts by mass of SBC, 6.8 parts by mass of SEBS, and 2.3 parts by mass of SEPS. Mix cycloolefin copolymer, SBC, SEBS and SEPS at 35°C, at a speed of 300 rpm, and mix for 5 minutes. Then, add the mixed material from the feeder to the twin-screw extruder for extrusion granulation. The process conditions are set as follows: feeder speed 8 rpm, screw speed 200 rpm, and extruder temperature of each section 180-230°C. After water cooling, pelletizing and drying, a cycloolefin copolymer composite material is obtained.

[0059] The test results are shown in Table 1.

[0060] Comparative Example 1

[0061] The untreated cycloolefin copolymer particles were added to a twin-screw extruder for extrusion granulation. The process conditions were set as follows: feeder speed 8 rpm, screw speed 200 rpm, and extruder section temperature 180-230°C. After water cooling, pelletizing and drying, the cycloolefin copolymer composite material was obtained.

[0062] The test results are shown in Table 1.

[0063] Table 1

[0064]

[0065] From Table 1, we can see that

[0066] (1) By comparing the test data of Examples 1 to 3 with Comparative Example 1, it can be seen that the addition of SBC elastomer alone has limited toughening effect on COC. From the results of the unnotched impact strength and elongation at break of Examples 2, 5 and 7, compared with Comparative Example 1, the synergistic toughening effect of SEBS and SEPS can significantly improve the toughness of COC. From the data of the length deviation and lateral deviation of the tensile spline, the dimensional deviation of the sample is significantly reduced after the addition of the elastomer, and the accuracy of spline preparation is improved.

[0067] (2) From the comparison of the unnotched impact strength of Example 2, Example 5, Example 6, and Example 7, when the ratio of SEBS to SEPS is 1:1, the unnotched impact strength of the spline is higher than that of the spline with more mass parts of SEBS added alone. When the same mass parts are added, the unnotched impact strength of the spline when the ratio of SEBS to SEPS is 3:1 is significantly higher than that of the spline with SEBS added alone, indicating that the two play a synergistic toughening role.

Claims

1. A cyclic olefin copolymer composite material, characterized in that: Contains the following ingredients:

2. The composite material according to claim 1, characterized in that The cycloolefin copolymer is a cycloolefin copolymer with a norbornene content of more than 70%.

3. The composite material according to claim 1, characterized in that The cycloolefin copolymer has a glass transition temperature of 70 to 160° C. and a melt flow rate of 4 to 50 g / 10 min.

4. The composite material according to claim 1, characterized in that The glass transition temperature is 131±5° C., and the melt flow rate is 45±5 g / 10 min.

5. The composite material according to claim 1, characterized in that The styrene-butadiene copolymer has a melt flow rate of ≥8g / 10min and a Vicat softening point of ≥85°C.

6. The composite material according to claim 1, characterized in that The hydrogenated styrene-butadiene-styrene copolymer has a styrene content of 30±5% and a hardness of less than 75.

7. The composite material according to claim 1, characterized in that The styrene-ethylene / propylene-styrene copolymer has a styrene content of 30±5% and a hardness of less than 80.

8. The composite material according to claim 1, characterized in that Also contains hydrogenated styrene-butadiene-styrene copolymer and styrene-ethylene / propylene-styrene copolymer.

9. The composite material according to claim 8, characterized in that The mass ratio of hydrogenated styrene-butadiene-styrene copolymer to styrene-ethylene / propylene-styrene copolymer is 2.5-3.5:

1.

10. The composite material according to claim 8, characterized in that The mass ratio of hydrogenated styrene-butadiene-styrene copolymer to styrene-ethylene / propylene-styrene copolymer is 3:1.

Citation Information

Patent Citations

  • Transparent toughened cycloolefin copolymer

    CN111393783A

  • High-toughness COC material and preparation method thereof

    CN111978665A

  • Toughened cyclic polyolefin material with high transparency and low dielectric loss and preparation method therefor

    WO2022105149A1